In vivo antiviral activity and pharmacokinetics of (-)-cis-5-fluoro-1-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine in woodchuck hepatitis virus-infected woodchucks. - Cullen, J M (1997)
The (-) enantiomer of cis-5-fluoro-1l-[2-(hydroxymethyl)-1,3-oxathiolan-5-yl]cytosine [(-)-FTC)], a substituted oxathiolane compound with anti-hepatitis B virus activity in vitro, was assessed for its efficacy in woodchucks with naturally acquired woodchuck hepatitis virus (WHV) infection. Pharmacokinetics and in vitro anabolism were also determined. (-)-FTC was anabolized to the 5'-triphosphate in a dose-related fashion, reaching a maximum concentration at about 24 h in cultured woodchuck hepatocytes. Following administration of a dose of 10 mg/kg of body weight intraperitoneally (i.p.), the clearance of (-)-FTC from plasma was monoexponential, the terminal half-life was 3.76 +/- 1.4 h, and the systemic clearance was 0.12 +/- 0.06 liters/h/kg. The antiviral efficacy of (-)-FTC in the woodchuck model was assessed by quantitation of serum WHV DNA levels and by WHV particle-associated DNA polymerase activity at two dosages, 30 and 20 mg/kg given i.p. twice daily (b.i.d.), respectively. The level of WHV DNA in serum was reduced 20- to 150-fold (average, 56-fold) in the 30-mg/kg-b.i.d. treatment group and 6- to 49-fold (average, 27-fold) in the 20-mg/kg-b.i.d. treatment group. Viral DNA polymerase levels diminished accordingly. One week after treatment was discontinued, WHV levels returned to pretreatment levels in both studies. These animals were biopsied before and following treatment with 30 mg of (-)-FTC per kg. Their livers were characterized by a mild increase in cytoplasmic lipid levels, but this change was not associated with altered liver enzyme levels. Serum chemistry and hematology results were within the normal ranges for all treated animals. We conclude that (-)-FTC is a potent antihepadnaviral agent and that it has no detectable toxic effects in woodchucks when given for up to 25 days. Further development of (-)-FTC as an anti-hepatitis B virus therapy for patients is warranted.